Leishmanicidal and trypanocidal activity of Sapindus saponaria (2014)
ABSTRACT: Leishmaniasis and trypanosomiasis are parasitic diseases with a high infection rate, being a serious public health issue in the new world. Unfortunately, there are few available commercial drugs, poorly efficient and with increasing parasite resistance. Under these conditions, there is a need for new molecules to develop new and better drugs. One approach to carry out this search is using traditional medicine as information source to obtain new molecules or extracts to control these parasite diseases. Sapindus saponaria (Sapindaceae) fruit resin is used in Colombia to treat ulcers caused by Leishmaniasis. In a bioguided study, we have analyzed the in vitro effect of fruit resin, chromatographical fractions from fruit resin and also pure compounds against Leishmania species (L. panamensis, L. braziliensis, L. amazonensis and L. donovani) and Trypanosoma cruzi. The in vivo antileishmanial effect was established under the hamster model for cutaneous leishmaniasis by L. panamensis; refined extract of S. saponaria and pure saponins displayed high in vitro and in vivo activity as leishmanicides. In addition, extracts caused low viability on T. cruzi amastigotes. The use of the crude extract can be a good alternative against cutaneous leishmaniasis, due to its activity, reduced hemolytic effect, and easy production procedures.